Lagenaria siceraria fruit: A review of its phytochemistry, pharmacology, and promising traditional uses - Saeed, Muhammad; Khan, Muhammad Sajjad; Amir, Kinza; Bi, Jannat Bi; Asif, Muhammad; Madni, Asadullah; Kamboh, Asghar Ali; Manzoor, Zahid; Younas, Umair; Chao, Sun (Frontiers in Nutrition, 2022)
For many centuries, the Cucurbitaceae family has been imparting a vital role being as a source of therapeutic medicines. Researchers have studied the various plants of this family due to their medicinal potential. Throughout the continent of Asia, different components of Lagenaria siceraria have been used as an ointment for the treatment of many ailments. The fruit of Lagenaria siceraria is rich in fat, carbohydrates, fiber, protein, calcium, and magnesium. Various properties that are beneficial for human health have been attributed to this plant like antioxidant, hypolipidemic, diuretic, laxative, hepatoprotective, analgesic, antihypertensive, cardioprotective, central nervous system stimulant, anthelmintic, free radical scavenging, immunosuppressive and adaptogenic. The species possess a diverse set of biological compounds like flavonoids, sterols, saponins, and terpenoids. The extracts of Lagenaria siceraria have been shown to have a variety of pharmacological properties. Lagenaria siceraria performs a wide range of pharmacological and physiological actions. The literature was taken from Pub-Med, Science Direct, Google scholar etc. showing the remarkable effects to treat human and animal illnesses due to its’ potent bioactive chemicals that have great medicinal potential. The key objective of this thorough analysis is to present a summary of the data about the beneficial and harmful effects of Lagenaria siceraria intake on human health, as well as in veterinary fields.